2018
DOI: 10.1039/c7tb03153j
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oxidative stress and sensitization of cancer cells to paclitaxel by gold nanoparticles with different charge densities and hydrophobicities

Abstract: Gold nanoparticles with various positive charge densities and hydrophobicities induce cellular oxidative stress differently and sensitize cancer cells to paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…A library of GNPs (6 nm) with continuously changing positive charge/negative charge density was constructed by varying the ratio of positively/negatively charged ligands to neutrally charged ligands. In HeLa, HEK293, and A549 cells, Su et al (2012)and Sun et al (2018) found that the level of GNP endocytosis was positively correlated with a positive charge density, while negative charge density had no significant influence on cellular uptake (Figure 2). Therefore, in multiple immune and non-immune cells, positively charged GNPs are more prone to endocytosis than are neutral and negatively charged GNPs.…”
Section: Surface Chargementioning
confidence: 94%
See 4 more Smart Citations
“…A library of GNPs (6 nm) with continuously changing positive charge/negative charge density was constructed by varying the ratio of positively/negatively charged ligands to neutrally charged ligands. In HeLa, HEK293, and A549 cells, Su et al (2012)and Sun et al (2018) found that the level of GNP endocytosis was positively correlated with a positive charge density, while negative charge density had no significant influence on cellular uptake (Figure 2). Therefore, in multiple immune and non-immune cells, positively charged GNPs are more prone to endocytosis than are neutral and negatively charged GNPs.…”
Section: Surface Chargementioning
confidence: 94%
“…In our previous study, cellular uptake level of hydrophobic and positively charged GNPs (6 nm) was positively correlated with oxidative stress level in A549 cells. Inhibition of GNPs' internalization led to the decrease of oxidative stress level, indicating that oxidative stress induced by GNPs is internalization-dependent (Sun et al, 2018). Therefore, for certain NPs, cellular uptake is positively correlated with cytotoxicity.…”
Section: Cellular Uptakementioning
confidence: 96%
See 3 more Smart Citations